Sistem Mekanisme Pemerolehan Naskah Novel Chicklit dan Teenlit Indonesia pada Tiga Penerbit - Redyanto Noor (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2018)
AbstractSome literary experts say that literary works are cultural objects and production is an industrial process. When literature enters the territory of production then the laws imposed upon itself are industrial law. That is why when talking about the production of literary works means dealing with laws (read: systems, mechanisms, and strategies) imposed by the institution of manufacture, i.e. publishers. Whereas in industrial business competition, every producing institution besides applying the conventional laws of industry, also develops distinctive internal laws to maintain the competitive power of its institution against the strength of other producing institutions.The modern publisher as a book-producing institution must creatively develop its industrial laws in order to compete with other similar publishers. Starting from the above references in chicklit and teenlit novel Indonesia's production article will discuss chicklit and teenlit novel production mechanism and mechanism covering three publishers, namely Elex Media Komputindo, GagasMedia, and Gramedia Pustaka Utama. The system and production mechanism in question includes the acquisition of the manuscript. Acquisition of manuscripts includes hunting and auction of manuscripts. IntisariBeberapa ahli sastra mengatakan bahwa karya sastra adalah obyek budaya dan produksi adalah proses industri. Ketika sastra memasuki wilayah produksi maka hukum yang dikenakan pada dirinya sendiri adalah hukum industri. Itulah mengapa ketika berbicara tentang produksi karya sastra berarti berurusan dengan hukum (baca: sistem, mekanisme, dan strategi) yang dikenakan oleh institusi manufaktur, yaitu penerbit. Sedangkan dalam persaingan bisnis industri, setiap lembaga produksi selain menerapkan hukum industri konvensional, juga mengembangkan undang-undang internal yang khas untuk mempertahankan daya saing lembaga mereka terhadap kekuatan lembaga produksi lainnya. Penerbit modern sebagai lembaga pembuat buku harus secara kreatif mengembangkan undang-undang industrinya agar dapat bersaing dengan penerbit lain yang serupa. Dari referensi di atas dalam novel chicklit dan teenlit, artikel ini akan membahas mekanisme dan mekanisme produksi novel chicklit dan teenlit yang meliputi tiga penerbit, yaitu Elex Media Komputindo, GagasMedia, dan Gramedia Pustaka Utama. Sistem dan mekanisme produksi yang dimaksud termasuk akuisisi naskah. Akuisisi manuskrip termasuk berburu dan melelang manuskrip.